UPAYA MITIGASI TURNOVER INTENTION DI SEKTOR PERBANKAN: Tindakan Evaluatif Pada Gaya Kepemimpinan, Stres Kerja, dan Kepuasan Kerja - Rahmat Fabli; Laura Syahrul; Harif Amali Rifai (Halu Oleo University, 2024)
Nowadays, turnover problem has increasing in almost every banking due to employee expectation growth for benefit and leadership implementation. Leadership implementation also found can affect job stress. Therefore, this study aims to evaluates and analyze the effect of transformational leadership on turnover intention by mediating contribution of job stress and job satisfaction. By using stratified proportionate random sampling technique to 152 permanent employees, then their responses analyze with Smart-PLS latest version software. Result found that five relationships were in-line with the research expectation, while the other two are not.